ANALISIS DAMPAK LALU LINTAS PENGEMBANGAN KORIDOR JALAN SRIWIJAYA SEMARANG - Hans Citra Naradwisari; Sarlita Ratna Putri; Epf Eko Yulipriyono; Supriyono Supriyono (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2016)
Sriwijaya region is an area of trade, services, commercial and residential in Semarang. This has sparked occurrence of resurgence, resulting in traffic jams in the area is increasing. The corridor of the Sriwijaya Street in existing condition is very crowded time in the morning, afternoon and evening due to the shopping centers, offices and residential. Because of these problems it will be planned traffic management, road widening and green design time. In this study will be discussed on the performance of existing traffic, traffic performance after the construction of the building, traffic performance in 2020 and traffic performance after application of some solutions will be used is the method of analysis MKJI 1997. Building area of amusement park, hotel and store is calculated to obtain resurgence happened. The amount of resurgence then charged on each road, after getting overburdened traffic volume resurgence performance analysis, intersection isn’t signalized and performance road intersection hotspot. From the amount list of vehicles from 2010 through 2014 found the rate of growth is 7,88 used to predict traffic conditions 5 years to come, so it can be selected solution that can solve problems up to 5 years. Test results are as follows traffic management course deemed unable to cope with traffic jams problems that occur so need to be widening at Jalan Sriwijaya and need to redesign the green time.